High temperature mechanical properties of laminated ZrB2–SiC based ceramics. Issue 16 (December 2016) - Wei, Chuncheng; Liu, Xinchao; Niu, Jinye; Feng, Liu; Yue, Hongzhi
Abstract: Two laminated ZrB2 -SiC based ceramics were prepared by tape casting and subsequent hot pressing, with BN (LZB) and graphite (LZG ) as interface layers. The LZB specimen presents flexural strength of 381 MPa at room temperature and 111 MPa at 1500 °C; while the LZG specimen shows flexural strength of 414 MPa at room temperature and 377 MPa at 1500 °C. In addition, the flexural strength of LZG specimen is always higher than that of the LZB specimen in the temperature range from room temperature to 1500 °C. Such higher strength is attributed to the healing of surface microcracks and pores by the SiO2 glass phase, producing less glass phase in graphite interface layers at high temperature.